2005
DOI: 10.1002/cbic.200500083
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of LXXLL‐Based Protein–Protein Interactions

Abstract: Protein-protein interactions between estrogen receptors, ERalpha and ERbeta, and their coactivators (CoAs) are an attractive target for drug intervention. This interaction is mediated by a small pentapeptide motif (LXXLL), termed the NR box. Based on this motif, a variety of cyclic and linear peptides were synthesized in order to gain a better understanding of the association of CoA proteins with the ER isoforms. Utilizing a time-resolved florescence-based coactivator interaction assay, we determined the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 33 publications
0
58
0
1
Order By: Relevance
“…A range of peptides, peptidomimetics, and nonpeptide small molecules that inhibit the activity of a variety of NHRs even when agonists are present has been designed over the past decade (Chang et al, , 2005Norris et al, 1999;Hall et al, 2000;Nguyen et al, 2002;Kern and Zuiderweg, 2003;Leduc et al, 2003;Pike et al, 2003;Geistlinger et al, 2004;Arnold et al, 2005Arnold et al, , 2007Galande et al, 2005;Wang et al, 2006;Estebanez-Perpina et al, 2007a;Mettu et al, 2007;LaFrate et al, 2008;Parent et al, 2008); these are sometimes referred to as coactivator binding inhibitors. Coactivator binding inhibitors target the receptor at a site spatially distinct from the orthosteric site, leading to modulation of receptor activity.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…A range of peptides, peptidomimetics, and nonpeptide small molecules that inhibit the activity of a variety of NHRs even when agonists are present has been designed over the past decade (Chang et al, , 2005Norris et al, 1999;Hall et al, 2000;Nguyen et al, 2002;Kern and Zuiderweg, 2003;Leduc et al, 2003;Pike et al, 2003;Geistlinger et al, 2004;Arnold et al, 2005Arnold et al, , 2007Galande et al, 2005;Wang et al, 2006;Estebanez-Perpina et al, 2007a;Mettu et al, 2007;LaFrate et al, 2008;Parent et al, 2008); these are sometimes referred to as coactivator binding inhibitors. Coactivator binding inhibitors target the receptor at a site spatially distinct from the orthosteric site, leading to modulation of receptor activity.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…Based on this scaffold, LXXLL-containing disulfide-bridge nonapeptides were reported with high affinity and selectivity for ERa (2 and 3, Figure 2.3). Introduction of nonnatural amino acids, notably the neopentyl glycine amino acid, in the cyclic peptides and optimization of binding affinity even resulted in peptide binders with a K i of only 70 pM [61]. In a following detailed study it was shown that a high helical content of the peptide not always correlates with higher affinity to the hydrophobic ER LBD coactivator-binding groove [61,62].…”
Section: Nonnatural Cyclic Peptidesmentioning
confidence: 99%
“…Introduction of nonnatural amino acids, notably the neopentyl glycine amino acid, in the cyclic peptides and optimization of binding affinity even resulted in peptide binders with a K i of only 70 pM [61]. In a following detailed study it was shown that a high helical content of the peptide not always correlates with higher affinity to the hydrophobic ER LBD coactivator-binding groove [61,62]. Cyclic peptides with other thiol-containing amino acids, such as homocysteine and penicillamine, were also studied.…”
Section: Nonnatural Cyclic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies using peptides and peptide mimics of the LXXLL motifs of the SRCs have demonstrated that this alternative approach is feasible. [13][14][15][16] If disruption of this helix-groove protein-protein interaction between the ERs and SRCs could be effected with small molecules, as is possible in other helix-groove interactions, 17-23 such molecules would be intriguing molecular probes for studying ER signaling. They might also afford an alternative strategy for blocking estrogen action in breast cancer less likely to be compromised by the cellular adaptations responsible for tamoxifen resistance.…”
Section: Introductionmentioning
confidence: 99%